2006
DOI: 10.1021/ol060473w
|View full text |Cite
|
Sign up to set email alerts
|

Mild and Direct Conversion of Quinoline N-Oxides to 2-Amidoquinolines with Primary Amides

Abstract: [reaction: see text] A simple, one-pot procedure is described for the direct conversion of quinoline N-oxides to alpha-amidoquinolines with primary amides. This methodology is complimentary to the Abramovich reaction, which is limited to the introduction of secondary amides via imidoyl chlorides. Although reaction conditions are quite similar, omission of the base is key for successful reaction with primary amides, which were found not to proceed through the intermediacy of an imidoyl chloride but rather throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 17 publications
(8 reference statements)
0
27
0
Order By: Relevance
“…Isocyanate was first shown to be a suitable reagent for the C2‐amidation of quinoline/isoquinoline N ‐oxides by Couturier and coworkers in 2006 (Scheme 22). [43] In this reaction, isocyanate 79 , generated via an in situ reaction between the primary amide and oxalyl chloride, undergoes 1,3‐dipolar cycloaddition with quinoline N ‐oxide 19 , followed by decarboxylative aromatization of the adduct to give 81 . Unfortunately, the strongly acidic conditions and long reaction times (typically>20 h) greatly limit the application of this reaction.…”
Section: Simple C2‐h‐functionalizationmentioning
confidence: 99%
“…Isocyanate was first shown to be a suitable reagent for the C2‐amidation of quinoline/isoquinoline N ‐oxides by Couturier and coworkers in 2006 (Scheme 22). [43] In this reaction, isocyanate 79 , generated via an in situ reaction between the primary amide and oxalyl chloride, undergoes 1,3‐dipolar cycloaddition with quinoline N ‐oxide 19 , followed by decarboxylative aromatization of the adduct to give 81 . Unfortunately, the strongly acidic conditions and long reaction times (typically>20 h) greatly limit the application of this reaction.…”
Section: Simple C2‐h‐functionalizationmentioning
confidence: 99%
“…A similar way for activation of primary amides consists of treating them with oxalyl chloride, resulting in highly reactive acyl isocyanates. [ 41 ]…”
Section: Deoxygenative C–h Functionalizationmentioning
confidence: 99%
“…A similar way for activation of primary amides consists of treating them with oxalyl chloride, resulting in highly reactive acyl isocyanates. [41] Several approaches for deoxygenative amidation of quinoline N-oxides with nitriles were developed (Scheme 23). [42][43][44] One of them is based on the activation of nitriles by an acid catalyst providing active nitrilium cations.…”
Section: Deoxygenative Aminationmentioning
confidence: 99%
“…An interesting development has been described by Couturier and coworkers, who reported that acyloyl isocyanates can be generated upon the action of oxalyl chloride on primary amides in the absence of base [109]. In the presence of base, a facile transformation of amide to nitrile occurs.…”
Section: Cycloaddition To Carbon-nitrogen Multiple Bondsmentioning
confidence: 99%